Thrombin generation in paediatric patients with congenital heart disease - Koestenberger, M.; Cvirn, G.; Rosenkranz, A.; Leschnik, B.; Raith, W.; Muntean, W. (Hämostaseologie, 2008)
Thrombin generation was studied in paediatric patients with congenital heart disease (CHD) undergoing cardiac surgery using the calibrated automated thrombography (CAT) in terms of the lag time until the onset of thrombin formation, time to thrombin peak maximum (TTP), endogenous thrombin potential (ETP), and thrombin peak height. The suitability to determine the coagulation status of these patients was investigated. Patients, material, methods: CAT data of 40 patients with CHD (age range from newborn to 18 years) were compared to data using standard coagulation parameters such as prothrombin (FII), antithrombin (AT), tissue factor pathway inhibitor (TFPI), prothrombin fragment 1.2 (F 1.2), thrombin-antithrombin (TAT), activated partial thromboplastin time (aPTT), and prothrombin time (PT). Results: A significant positive correlation was seen between ETP and FII (p < 0.01; r = 0.369), as well as between peak height and F II (p < 0.01; r = 0.483). A significant negative correlation was seen between ETP and TFPI values (p < 0.05; r = –0.225) while no significant correlation was seen between peak height and TFPI. A significant negative correlation was seen between F 1.2 generation and ETP (p < 0.05; r = –0.254) and between F 1.2 generation and peak height (p < 0.05; r = –0.236). No correlation was seen between AT and ETP or peak. Conclusions: CAT is a good global test reflecting procoagulatory and inhibitory factors of the haemostatic system in paediatric patients with CHD.
Keywords: Kalibrierte automatisierte Thrombographie; Thrombinentstehung; endogenes Thrombinpotenzial; Prothrombin; Herzoperation; angeborene Herzfehler